Women's participations in economic and NGO activities in Bangladesh: An empirical study on the Bangladesh Demographic and Health Survey (BDHS). Issue 7 (11th July 2016) - Khan, Hafiz T.A.; Rahman, Twyeafur
Abstract : Purpose: – The purpose of this paper is to examine key factors affecting the economic involvement of women in Bangladesh and women's involvement with non-governmental organisations (NGOs) particularly in microcredit operating in that country. Design/methodology/approach: – The study uses nationally representative data set. Quantitative analysis was utilised to explore data contained in the Bangladesh Demographic and Health Surveys 2007 and 2011. Findings: – The findings indicate that age, marital status, number of children living in the household, place of residence, geographical location, education, partner's education and the wealth index are important factors in enabling women's involvement in economic activities. In other words, the key findings emerged from the study are first, the low level of women's economic activities in Bangladesh with a majority involved in farming, agriculture and poultry; second, those women involved in the labour market generally tended to come from poor backgrounds, have very little education, live in the Northwest geographical region and have a large family living in the same house; and finally, age, currently married, having a higher number of children, living in rural areas, from the Northwest region with almost no education and belonging to the poor wealth index quintile are found to be associated more with NGO activities in Bangladesh. Social implications: – The findings indicate there are potential barriers that are preventing Bangladeshi women from engaging in the labour market that could reinforce the case for reshaping the government's labour policies. The study reveals that the recent economic crisis has no significant impact on the women labour force participation as well their involvement in NGO activities in Bangladesh. It is generally understood that enhancing women's economic participation and NGO activities has a positive impact at family, community and country levels. The study concludes that investing in women, particularly in creating employment opportunities including NGO sectors can help the country as a safeguard even during the economic crisis. It is anticipated that the findings will help policy-makers in enhancing female labour force participation as well as encouraging them to engage in NGO activities in Bangladesh. Originality/value: – The research paper is original in terms of conceptual framework, research design and statistical analysis.